1996
DOI: 10.1111/j.1476-5381.1996.tb15676.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N‐, P‐ and Q‐type neuronal calcium channel antagonists on mammalian peripheral neurotransmission

Abstract: 1 The effects of N-, P-and Q-type neuronal voltage-operated calcium (Ca2") channel antagonists on neurotransmission were determined in a range of cardiovascular and urogenital tissues, as well as the diaphragm, isolated from rat or mouse. 2 The pharmacological tools chosen were co-conotoxin GVIA (CTX GVIA), a selective N-type Ca21 channel antagonist, the P-type channel blocker (< 100 nM) w0-agatoxin IVA (AGA IVA) and coconotoxin MVIIC (CTX MVIIC), a non-selective antagonist of N-, P-and Q-type channels. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 43 publications
2
51
2
Order By: Relevance
“…The average s.e.mean within tissues (or rabbits) was calculated from repeated measures analysis of variance (ANOVA) using the pooled estimate of error from the residual mean square as (error mean square/number of tissues, or rabbits) 0.5 after sums of squares between tissues (or rabbits) and between peptide concentrations (or times) had been subtracted from the total sums of squares for each treatment group (Snedecor & Cochran, 1989). These average s.e.means are located on the lines shown in Figures 1, 4 and 5 (Wright et al, 1987;Wright & Angus, 1996). For rat atrium, mesenteric artery and vas deferens experiments, sympathetic responses were compared within and between groups by repeated measures ANOVA with Greenhouse-Geisser correction for correlation (Ludbrook, 1994), calculated by means of the statistical program SuperANOVA TM 1.11 for Macintosh.…”
Section: Analyses and Statistical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average s.e.mean within tissues (or rabbits) was calculated from repeated measures analysis of variance (ANOVA) using the pooled estimate of error from the residual mean square as (error mean square/number of tissues, or rabbits) 0.5 after sums of squares between tissues (or rabbits) and between peptide concentrations (or times) had been subtracted from the total sums of squares for each treatment group (Snedecor & Cochran, 1989). These average s.e.means are located on the lines shown in Figures 1, 4 and 5 (Wright et al, 1987;Wright & Angus, 1996). For rat atrium, mesenteric artery and vas deferens experiments, sympathetic responses were compared within and between groups by repeated measures ANOVA with Greenhouse-Geisser correction for correlation (Ludbrook, 1994), calculated by means of the statistical program SuperANOVA TM 1.11 for Macintosh.…”
Section: Analyses and Statistical Methodsmentioning
confidence: 99%
“…CVID was 10 fold less potent in the mesenteric artery preparation compared with the vas deferens or atrium assay. Importantly, the sympathetic nerves were stimulated with parameters that were N-type voltage-operated calcium channel blocker-sensitive (100%) to avoid confounding the assay estimate of pIC 50 with N-channel-resistant (perhaps P/Q channel-sensitive) responses (see Wright & Angus, 1996;Sanger et al, 2000). These isolated tissue assays allowed a direct comparison of oset rates of CVID and MVIIA in three tissues.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…Moreover, different voltage-gated calcium channels can be coupled to transmitter release during low-versus highfrequency electrical stimulation (Wright and Angus, 1996). Therefore, we next sought to determine the requirement for specific voltage-activated calcium channels in BDNF release evoked by different patterns of stimulation.…”
Section: Release Of Native Bdnf Evoked By Patterned Electrical Stimulmentioning
confidence: 99%
“…Of the multiple subtypes of voltage-gated calcium channel current (I Ca ), it has been shown that calcium influx via the N-, P, and Q-subtypes triggers neurotransmission at central and peripheral synapses (Luebke et al, 1993;Takahashi and Momiyama, 1993;Regehr and Mintz, 1994;Wheeler et al, 1994;Waterman, 1996;Wright and Angus, 1996). N-type channels are identified pharmacologically as being blocked irreversibly by -conotoxin GVIA (-Cgtx GVIA) (McCleskey et al, 1987;Plummer et al, 1989) and are encoded for by the class B ␣ 1 subunit gene (Dubel et al, 1992;Williams et al, 1992).…”
Section: Abstract: Calcium Channel; G-protein; Atp; Inhibition; Patcmentioning
confidence: 99%